What the moon said - Rosengren, Gayle (G.P. Putnam's Sons, an imprint of Penguin Group (USA) Inc., 2014)
When Esther's family moves to a farm during the Great Depression, she soon learns that there are things much more important than that her superstitious mother rarely shows her any affection.